2013
DOI: 10.1007/s13762-012-0151-6
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of variations in benzene concentration produced from vehicles and gas stations in Tehran using GIS

Abstract: This study investigates the variations of benzene concentration levels in district 1, situated in the north part of Tehran, capital of Iran. Thirty-three stations in five categories, namely roadsides, busy roads, residential areas, traffic intersections, and the vicinity of gas stations, were monitored during the rush hours in the afternoon once a week over a period of 1 year. Accordingly, benzene concentration levels were measured and predicted by inverse distance weight model. The recorded benzene concentrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 44 publications
1
5
0
1
Order By: Relevance
“…Points closer to the interpolated point obtain greater weighting values. As the distance increases, assigned weights to known points decline and as the power parameter rises, this effect decreases [27]. In this paper, the power value was considered as 2.…”
Section: Methodsmentioning
confidence: 99%
“…Points closer to the interpolated point obtain greater weighting values. As the distance increases, assigned weights to known points decline and as the power parameter rises, this effect decreases [27]. In this paper, the power value was considered as 2.…”
Section: Methodsmentioning
confidence: 99%
“…Jafari and Ebrahimi () reported that the average concentration of benzene in Tehran fluctuated from 3.2 ppb (0.011 mg/m 3 ) to 156 ppb (0.536 mg/m 3 ). Atabi, Moattar, Mansouri, Alesheikh, and Mirzahosseini () investigated the contribution of benzene to air pollution of Tehran. The annual concentrations of benzene were as follows: in paths with heavy traffic, 13.85 ppb; in the intersections, 14.98 ppb; in the vicinity of gas stations, 29.01 ppb; in residential areas, 3.26 ppb; and along roadsides, 9.97 ppb, in Atabi et al.’s study.…”
Section: Resultsmentioning
confidence: 99%
“…Vlachopoulou et al (2001) used the GIS tool to select warehouse sites. Atabi et al (2013) investigated levels of benzene concentration produced from vehicles and gas stations at Tehran in Iran by using the GIS tool. The data for this study were classified into two categories for grid analysis: internal demand factors and external demand factors.…”
Section: Building Base Data For Gis Analysismentioning
confidence: 99%